Sea Ice melting in Arctic - Song, Yongjia (Arctic Portal, 2011)
Yongjia Song, University of Wisconsin-Madison, USA / China, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.